Hypercoagulability in COVID-19 - Wessels, Pieter (SA Heart Journal, 2020)
COVID-19 is associated with a hypercoagulable state that may present as pulmonary thrombosis, pulmonary embolism, and venous and arterial thrombosis. Suggested pathogenesis include direct infection of the endothelial cell with subsequent endothelial cell dysfunction, leading to increased procoagulant activity, decreased anticoagulant activity and decreased fibrinolysis. The severe immune inflammatory response in the lungs with cytokine release also plays a critical role (immunothrombosis). Hypoxia has a local and systemic effect on coagulation. Various markers of this state have been described, and especially the D-dimer level (and rapid changes in the D-dimer level) as a reliable prognostic marker. It is also used as indicator for initiation of anticoagulation by some experts. Due to the pleotrophic effects of heparin, it is the anticoagulant of choice for these patients (most often low molecular weight heparin, due to decreased risk of heparin induced thrombocytopenia, ease of use). No clinical trial data is available at the time of writing (28 May 2020), and suggested guidelines of experts in different countries are discussed.